Self-Inflicted Cut-Throat Injuries in Psychiatric Patients During the COVID-19 Pandemic: A Report of Two Rare Cases - Anurag Kumar; Khan Vakil; Anil KUMAR; Majid Anwer; Sanjay Kumar; Deepak Kumar; Rekha Kumari (Bulletin of Emergency and Trauma, 2025)
Suicidal cut-throat injuries are rare in Indian society, as reported by the National Crime Records Bureau (NCRB). However, during the COVID-19 pandemic, a significant rise in unemployment among Indian youth led to increased psychological distress and depression, contributing to a surge in suicide cases, including those presenting with cutthroat injuries in emergency departments. This study reported two distinct cases of suicidal cutthroat injuries, both involving young individuals who were unemployed during the pandemic and suffered from underlying psychiatric disorders. Both patients presented with severe neck injuries, requiring immediate and complex intervention. Their conditions were further complicated by the psychological trauma associated with their mental health disorders. The management of these cases required a multidisciplinary approach, involving emergency medical care, surgical intervention, and psychiatric support. Both patients received prompt attention and stabilization, followed by psychological counseling and long-term psychiatric care. Their recovery was closely monitored, with a focus on addressing the root causes of their distress. These cases highlighted the increasing incidence of suicidal cutthroat injuries during the COVID-19 pandemic and emphasized the need for a comprehensive, multidisciplinary approach to managing both the physical and psychological aspects of such critical situations. This report underscored greater attention to mental health, particularly among the unemployed youth during crises.